Association between sociodemographic factors, working experience and training status with knowledge level towards food and personal hygiene among food handlers in Kuala Lumpur, Malaysia - R., Shalinawati; N. A., Mohamed; T. Jamaluddin, T. Z. M.; S., Shahlan (International Organization Of Scientific Research (IOSR), 2016)
Food borne illness seems to become more common in Malaysia. Thus, food handlers as the most important person need to play their role in providing safe food for their customers. Hence, nowadays it is compulsory for them to undergo food training course in order to gain knowledge on food and personal hygiene. However, not only training can affect level of knowledge but also working experience and socio-demographic characteristics. The purpose of this study was to determine the association between socio-demographic factors, working experience and training status with knowledge level towards food and personal hygiene among 180 food handlers who attended the vaccination programme in Dewan Bandaraya Kuala Lumpur (DBKL) clinic. The data were collected from 180 food handlers through the methods of questionnaire and analysed using the Statistical Package for Social Sciences (SPSS) version 21 for Windows. Based from the total answer answered by total 180 respondents, 96.11% score more than 80% of total questions correct ly, indicating that majority of the food handlers have a good knowledge on food and personal hygiene with frequency of 174. In the demographic profile analysis showed there is no association between socio-demographic factors and knowledge when. While analysis test showed there was significant difference for knowledge based on working experience. The results showed that only working experience is associated with knowledge.